The Role of Organisational Climate in Employee Well-Being and the Occurrence of Workplace Violence: Contextualisation of Theoretical Constructs - Butvilas, Tomas; Janiukštis, Andrius; Bubnys, Remigijus; Lūžienė, Rita (Social Welfare: Interdisciplinary Approach, 2023)
Research has shown the importance of microclimates for employee behaviour, organisational performance and individual employee well-being; also, the negative implications of workplace violence for organisational microclimate and employee well-being. This paper aims to shed light on the theoretical aspects of organisational microclimate, employee well-being and workplace violence, and to offer theoretical insights into the role of microclimate in employee well-being and the occurrence of workplace violence. To achieve this objective, an analysis and synthesis of recent scientific publications was chosen. The results revealed the theoretical links between the organisational microclimate and the emergence of workplace violence, as well as the negative implications of workplace violence for employee well-being and the further spread of violence in the organisation. This study will contribute to further empirical research on the role of organisational microclimate in employee well-being and the emergence of workplace violence.